How Traditional oil Miners Reach their Prosperity? – an Assessment of Social Welfare in Wonocolo, Indonesia - Tuzyahroya, Yeti Ulfah; Sariffuddin, S (KOMUNITAS: International Journal of Indonesian Society and Culture, 2020)
Traditional mining is one of the activities serving as a motor of economic growth of regional development so that its management should be able to give people prosperity. Mining activities, however, have limited production in which the community cannot permanently depend on it as what occurs in the traditional mining in Wonocolo. This study aimed to determine the level of welfare of the traditional oil and gas mining community in Wonocolo Village, Kedewan, Bojonegoro. The research was a mixed method research of which method design used validating quantitative data model design. The result of quantitative analysis which was the scoring would be validated with the description of qualitative data. The results of this study indicated that the welfare hierarchy of the traditional oil and gas mining community in Wonocolo was in the level of ultimate means to intermediate means. The community still prioritized physiological fulfillment needs rather than the needs for self-development. On the other hand, the fulfillment of basic needs taken from nature in Wonocolo was also vulnerable because the water and air were contaminated by oil. In addition, the nature of oil that is non-renewable and unsustainable has caused the Wonocolo community vulnerable.